Long-range allosteric regulation of the human 26S proteasome by 20S proteasome-targeting cancer drugs - David Haselbach; Jil Schrader; Felix Lambrecht; Fabian Henneberg; Ashwin Chari; Holger Stark (Nature Communications, 2017)
The proteasome regulates several important cellular processes and has been identified as a target for therapeutic interventions. Here the authors map the conformational and energy landscape of the 26S proteasome upon Oprozomib binding and uncover long-range allosteric effects that control the dynamic behaviour of the proteasome.